2007
DOI: 10.1139/h07-076
|View full text |Cite
|
Sign up to set email alerts
|

Minimal whey protein with carbohydrate stimulates muscle protein synthesis following resistance exercise in trained young men

Abstract: Whey protein is a supplemental protein source often used by athletes, particularly those aiming to gain muscle mass; however, direct evidence for its efficacy in stimulating muscle protein synthesis (MPS) is lacking. We aimed to determine the impact of consuming whey protein on skeletal muscle protein turnover in the post-exercise period. Eight healthy resistance-trained young men (age=21+/-1 .0 years; BMI=26.8+/-0.9 kg/m2 (means+/-SE)) participated in a double-blind randomized crossover trial in which they pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 44 publications
4
66
1
4
Order By: Relevance
“…In comparison to other protein sources, whey protein has greater bioavailability and solubility along with a higher concentration of branched-chain amino acid (BCAA), specifically leucine [2,1,3]. Findings from two previous meta-analyses of randomized controlled trials (RCTs) support the positive effect of high quality protein supplementation, including whey, to maximize the increase in muscle mass [4,5] and strength [4] when combined with prolonged (≥4 weeks) resistance training interventions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison to other protein sources, whey protein has greater bioavailability and solubility along with a higher concentration of branched-chain amino acid (BCAA), specifically leucine [2,1,3]. Findings from two previous meta-analyses of randomized controlled trials (RCTs) support the positive effect of high quality protein supplementation, including whey, to maximize the increase in muscle mass [4,5] and strength [4] when combined with prolonged (≥4 weeks) resistance training interventions.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, although several studies have analyzed the effect of whey protein supplementation on resistance training performance and outcomes [6][7][8][9], only some of them have specifically focused on resistance training individuals [10,11,3,12]. Indeed, only a few studies were focused on recreationally or well strength-trained athletes, and have reported a positive effect of whey, administered alone or combined with other nutrients, to maximize strength [13,2], lean body mass (LBM) or fat free mass (FFM) gains [2,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whey protein extract, because of its increased bioavailability and solubility, and its higher percentage content of EAA including BCAAs, specifically Leucine, has been proposed as the best optimal form of protein for strength and power athletes [17,45,51]. Although several studies have analysed the effect of whey protein supplementation on resistance training performance and outcomes only some of them have focused on resistance trained individuals [12,17,23,24,26,38,52,53].…”
Section: Documented Effects Of Whey Protein Supplement To Optimize Rementioning
confidence: 99%
“…Although some studies have shown greater strength, muscular hypertrophy and/or Lean Body Mass (LBM) gains when resistance training is combined with whey protein alone or in conjunction with carbohydrates other protein sources enriched with amino acids or creatine; there are still some inconsistencies regarding the most appropriate effective doses and ingestion-timing strategy for optimizing resistance training induced adaptations and outcomes (strength gain or muscle mass accretion) [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%